2013
DOI: 10.5121/ijmvsc.2013.4103
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Management Of Rice In India: A Rice Processing Company's Perspective

Abstract: The paper deals with the practical issues which exist in the supply chain of rice. The paper discusses various issues related to collaboration at downstream end of the supply chain, inventory management, demand consolidation and inventory reduction. While dealing with the supply chain issue it also gets into deal with the various procurement issues and finally a redesigned supply chain model has been proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…This is because it faces many supply chain problems related to procurement, distribution, collaboration etc. (Sharma et al 2013). Recent studies in agri-food supply chains conducted have explored into issues like technological advancements like Radio Frequency Identification (RFID) (Costa et al 2013;Verdouw et al 2014); traceability issues (Aung and Chang, 2014); sustainability (Beske et al 2014, Fayet andVermeulen, 2014;) etc.…”
Section: Agri-food Supply Chainsmentioning
confidence: 99%
“…This is because it faces many supply chain problems related to procurement, distribution, collaboration etc. (Sharma et al 2013). Recent studies in agri-food supply chains conducted have explored into issues like technological advancements like Radio Frequency Identification (RFID) (Costa et al 2013;Verdouw et al 2014); traceability issues (Aung and Chang, 2014); sustainability (Beske et al 2014, Fayet andVermeulen, 2014;) etc.…”
Section: Agri-food Supply Chainsmentioning
confidence: 99%
“…The relationship structure of organic red rice supply chain through PT Lingkar Organik Indonesia was formed by eight actors: farmers, collecting trader, PT Lingkar Organik Indonesia, Pamella Supermarkets, Maga Swalayan, Progo Store, Mirota, and consumers. The number of actors in the red rice supply chain is in line with [13] who shows that the rice supply chain structure in India works on a traditional framework that involves many intermediaries in the supply and distribution sector so that the supply chain becomes less efficient. Research from [14] also shows that there was many actors involved in the rice chain in Solok.…”
Section: The Relationship Structure Of the Organic Red Rice Supply Chainmentioning
confidence: 68%
“…A principle of taking a single variety for seed production in a village is also observed. Sharma et al, (2013) have reported the practical issues which exist in the supply chain of rice.…”
Section: Seed Distributionmentioning
confidence: 99%